2021
DOI: 10.1002/jev2.12117
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicle‐mediated endothelial apoptosis and EV‐associated proteins correlate with COVID‐19 disease severity

Abstract: Coronavirus disease-2019 (COVID-19), caused by the novel severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), has lead to a global pandemic with a rising toll in infections and deaths. Better understanding of its pathogenesis will greatly improve the outcomes and treatment of affected patients. Here we compared the inflammatory and cardiovascular disease-related protein cargo of circulating large and small extracellular vesicles (EVs) from 84 hospitalized patients infected with SARS-CoV-2 with differe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(103 citation statements)
references
References 79 publications
9
88
0
Order By: Relevance
“…When stratifying COVID‐19 patients with severe disease by mortality, no differences in EV‐TF‐activity was noted, as the level of EV‐TF‐activity was approximately 50 pM in both survivors and nonsurvivors. 131 These data appear to contrast with Guervilly et al., 36 who reported far lower levels of EV‐associated TF‐activity in COVID‐19. While the discrepancy might be explained by an overestimation of TF activity measured with commercial assays in absence of blocking antibodies to ensure of the specificity of the measurements, 132 , 133 , 134 these studies suggest that high EV‐TF activity may be associated with increased severity and mortality in COVID‐19.…”
Section: The Contribution Of Pevs To Covid‐19mentioning
confidence: 73%
See 2 more Smart Citations
“…When stratifying COVID‐19 patients with severe disease by mortality, no differences in EV‐TF‐activity was noted, as the level of EV‐TF‐activity was approximately 50 pM in both survivors and nonsurvivors. 131 These data appear to contrast with Guervilly et al., 36 who reported far lower levels of EV‐associated TF‐activity in COVID‐19. While the discrepancy might be explained by an overestimation of TF activity measured with commercial assays in absence of blocking antibodies to ensure of the specificity of the measurements, 132 , 133 , 134 these studies suggest that high EV‐TF activity may be associated with increased severity and mortality in COVID‐19.…”
Section: The Contribution Of Pevs To Covid‐19mentioning
confidence: 73%
“…Given the high prevalence of thrombosis in COVID‐19, 30 , 31 , 32 TF activity associated with EVs and its involvement in COVID‐19 pathology is of high interest. 36 , 70 , 118 , 130 Several studies 36 , 70 , 118 , 131 report a significant increase in TF activity associated with EVs from COVID‐19 patients when compared with healthy controls. Moreover, EV‐TF activity was significantly higher in COVID‐19 than in sepsis.…”
Section: The Contribution Of Pevs To Covid‐19mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to observations of elevated circulating EV numbers and their associations with disease severity, first studies reported a specific surface antigen signature [220] or protein cargo [222] in circulating EVs isolated from patients diagnosed with COVID-19. It also was speculated that changes in EV cargo in subgroups of COVID-19 patients, such as those with diabetes mellitus, obesity or hypertension, may contribute to the increased morbidity and mortality observed in these high-risk populations [223].…”
Section: Extracellular Vesicles and Thrombosis Associated With Covid-19 Infectionmentioning
confidence: 99%
“…It also was speculated that changes in EV cargo in subgroups of COVID-19 patients, such as those with diabetes mellitus, obesity or hypertension, may contribute to the increased morbidity and mortality observed in these high-risk populations [223]. Importantly, addition of plasma from severely-ill patients with COVID-19 to endothelial cells ex vivo was found to transfer a prothrombotic phenotype and to induce apoptotic cell death [222] suggesting the presence of a vicious cycle between endothelial injury and EV release in COVID-19 associated thrombosis.…”
Section: Extracellular Vesicles and Thrombosis Associated With Covid-19 Infectionmentioning
confidence: 99%